Design of a Pharmacokinetics Observer Through the Inversion of Pharmacodynamics in Intravenous General Anesthesia - Ramos Mendoza, Juan Pablo; Orozco Lopez, Juan Onofre; Rodríguez Herrero, Agustín (Revista Mexicana de Ingenieria Biomedica, 2025)
In this work, the feasibility of a state-space observer applied to a cohort of virtual patients in a simulator developed in Matlab-Simulink is tested. The modeling of virtual patients can be divided into a linear part, referred to as pharmacokinetics, and a nonlinear part, corresponding to pharmacodynamics. The state-space observer is designed to estimate the state variables, or masses in the compartments associated with the pharmacokinetics of the drugs Propofol and Remifentanil. Additionally, an observer for the state variables of the pharmacokinetics of Rocuronium is integrated to make all variables available for the design and implementation of control algorithms based on state variable feedback for the coadministration of the drugs. To complete the estimation scheme for the variables comprising the mathematical modeling of the virtual patients, an approximation of the inverse functions of the nonlinear elements modeling pharmacodynamics is included; this approximation is obtained using the System Identification Toolbox. The proposed scheme and the results obtained demonstrate its feasibility and open the door to future developments in the control of anesthesia systems.